Low incidence of recurrent Buruli ulcers in treated Australian patients living in an endemic region. - James W Wynne; Timothy P Stinear; Eugene Athan; Wojtek P Michalski; Daniel P O'Brien (Public Library of Science (PLoS), 2018)
We examined recurrent Buruli ulcer cases following treatment and assumed cure in a large cohort of Australian patients living in an endemic area. We report that while the recurrence rate was low (2.81 cases/year/1000 population), it remained similar to the estimated risk of primary infection within the general population of the endemic area (0.85-4.04 cases/year/1,000 population). The majority of recurrent lesions occurred in different regions of the body and were separated by a median time interval of 44 months. Clinical, treatment and epidemiological factors combined with whole genome sequencing of primary and recurrent isolates suggests that in most recurrent cases a re-infection was more likely as opposed to a relapse of the initial infection. Additionally, all cases occurring more than 12 months after commencement of treatment were likely re-infections. Our study provides important prognostic information for patients and their health care providers concerning the nature and risks associated with recurrent cases of Buruli ulcer in Australia.